The Relationship Between Nurses' Quality of Work-Life on Organizational Loyalty and Job Performance in Saudi Arabian Hospitals: A Cross-Sectional Study - Al-Dossary, Reem N (Frontiers in Public Health, 2022)
Purpose The purpose of this study is to analyze the relationship between quality of work-life on the organizational loyalty and job performance in Saudi Arabia. Methods This study used a cross-sectional design for collecting the data related to the nurses' quality of work-life, organizational loyalty, and job performance from nursing staff in Saudi Arabian hospitals. Three questionnaires were used in this study, which includes Quality of Work Life Scale (QWLS), Organizational Commitment Questionnaire (OCQ), and Individual Work Performance Questionnaire (IWPQ). An online version of the survey questionnaire was generated using the Google survey, to which a link is generated for collecting data. At the end of the survey, 243 responses were received. After removing the incomplete responses, 209 responses were considered for the data analysis. The statistical techniques including t-tests and Pearson's correlation were used in the data analysis. Results Nurse managers reflected good quality of life, and high loyalty toward their employers, and also reflected good job performance levels. However, staff nurses reflected poor quality of work-life, organizational loyalty, and job performance. Training and development had strong positive correlation with continuance commitment (r = 0.628, p < 0.01). Job satisfaction and job security held strong positive correlation with task performance (r = 0.601, p < 0.01) and contextual performance (r = 0.601, p < 0.01). Conclusion Quality of work-life, organization loyalty, and job performance are positively correlated, and poor quality of work-life can negatively impact job performance and organizational loyalty of nurses.